Artefakte des Entwerfens Skizzieren, Zeichnen, Skripten, Modellieren : 2., aktualisierte Auflage - Lyngsø Christensen, Rikke (Forum Architekturwissenschaft, 2022)
The conference proceedings are a collection of contributions from the 4th Forum Architekturwissenschaft on architectural design and its artifacts. The Conference was held in November, 2017 at the TU Berlin. Contributors to the present publication are interested in the epistemic potential of sketches, renderings, models, photographs and drawings in architectural design. All follow the thesis that media in the draft not only depict, but in turn are the basis of further acts of knowledge. Using case studies ranging from the Middle Ages to the present, the texts trace the particular qualitative influence that "making" a design has on the artifact for this design. The structure for both the conference and this publication came out of the attempt to bring together theoretical positions and the results of practical work - artifacts: The conference was associated with an exhibition at the Museum of Architecture of the TU Berlin and in the present volume, theoretical contributions alternate with textual descriptions of the shown artifacts.